CRISPR/Cas9-Mediated Integration of Large Transgene into Pig CEP112 Locus. Issue 2 (1st February 2020) - Li, Guoling; Zhang, Xianwei; Wang, Haoqiang; Mo, Jianxin; Zhong, Cuili; Shi, Junsong; Zhou, Rong; Li, Zicong; Yang, Huaqiang; Wu, Zhenfang; Liu, Dewu
Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein 9 (Cas9) is a precise genome manipulating tool that can produce targeted gene mutations in various cells and organisms. Although CRISPR/Cas9 can efficiently generate gene knockout, the gene knock-in (KI) efficiency mediated by homology-directed repair remains low, especially for large fragment integration. In this study, we established an efficient method for the CRISPR/Cas9-mediated integration of large transgene cassette, which carries salivary gland-expressed multiple digestion enzymes (≈ 20 kbp) in CEP112 locus in pig fetal fibroblasts (PFFs). Our results showed that using an optimal homology donor with a short and a long arm yielded the best CRISPR/Cas9-mediated KI efficiency in CEP112 locus, and the targeting efficiency in CEP112 locus was higher than in ROSA26 locus. The CEP112 KI cell lines were used as nuclear donors for somatic cell nuclear transfer to create genetically modified pigs. We found that KI pig (705) successfully expressed three microbial enzymes (β-glucanase, xylanase, and phytase) in salivary gland. This finding suggested that the CEP112 locus supports exogenous gene expression by a tissue-specific promoter. In summary, we successfully targeted CEP112 locus in pigs by using our optimal homology arm system and established a modified pig model for foreign digestion enzyme expression in the saliva.